PENGARUH JENIS KEMASAN TERHADAP KARAKTERISTIK FISIKOKIMIA DAN SENSORI KOPI ARABIKA GAYO DENGAN METODE PENGOLAHAN SEMI BASAH - Silaban, Rutdiani; Sinaga, Hotnida; Karo-Karo, Terip (Faculty of Agricultural Technology, Universitas Semarang, 2023)
Indonesia is the 4th largest coffee producer after Brazil, Vietnam and Colombia. The largest Arabica coffee production center in Indonesia is in Central Aceh District. Biophysical factors, such as soil conditions, climate and altitude, which are planted at an altitude of 1,000-1,400 meters above sea level are the factors that make Gayo Arabica coffee green bean known as a special coffee that has a strong coffee taste and characteristics. Coffee has a lot of chemical content in it, for example the content of chlorogenic acid and caffeine. Physicochemical analysis of the samples included moisture content, ash content, fat content, protein content, caffeine content, phenol content, acidity level (pH), and specific volume. This data analysis used a completely randomized design with 3 replications comparing coffee from each coffee processing using five types of storage packaging for 4 months. Semi-wet processed coffee has the characteristics of moderate acidity, sweet taste, medium to low. Keywords: Gayo Arabica, semi washed, green bean, storage, Packaging